The Use of ICT in Teaching English at UNIPDU Jombang - Achmad Fanani (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
This paper discussed the use of ICT in teaching English by the teachers at UNIPDU Jombang, more specifically about (1) the method of applying ICT in teaching English and (2) The reasons for using e-learning. The result of observation and interview with the teachers showed that: First, both English teachers being observed explained to the students the importance of English in the internet world. Second, the teachers at UNIPDU modeled how to use the internet for learning English. Third, the observed English teachers at UNIPDU explained to the students that a lot of questions and other sources of learning are available on the Internet. Fourth, The English teachers explained that they chose the problems or questions that suit the students’ English level of competence. Fifth, English teachers should give the opportunity to the students to communicate with them directly via social networking loved by youngsters nowadays like WA, Facebook or Twitter. Sixth, English teachers may give assignments to the students to look for the answers or solution to certain problems or questions on the internet.